Decision Support System for Selection of High-Aching Students Using Simple Additive Weighting Method - Thamrin, Karim; Parenreng , Jumadi Mabe; Haripuddin, Haripuddin (Internet of Things and Artificial Intelligence Journal, 2025)
Determination of outstanding students is done manually and tends to be subjective. This has shortcomings that cause several problems, namely, it takes a long time and requires energy for manual data processing, then requires extra care and thought in processing student value data. This study aims to produce a decision support system for selecting outstanding students with a matrix normalization process to a scale that can be compared with all existing alternative ratings using ISO 25010 with 8 testing aspects. This development uses the Waterfall model with research steps, namely: 1) Requirement, 2) Design, 3) Implementation, 4) Verification, and 5) Maintenance. In the early stages, researchers seek information related to user needs for the system to be created. Furthermore, the media design is designed based on the results of the needs analysis, after which the media is developed. The final stage is testing. Data collection instruments are conducted through Observation, interviews, and questionnaires. The data analysis technique used is based on the 8 testing characteristics in ISO 25010. The results of the functional suitability aspect test with a result of 98.6% of the criteria "Very Eligible". Performance efficiency testing with a result of 85.2% of the category grade B which is categorized as "Good". Usability testing of the percentage of user responses with a result of 84% of the criteria "Very Good". The results of the compatibility test show that the system has been successfully run on several versions of the browser well and does not cause problems when accessing the system. The results of the security test show that the system has good security with a grade of B. Based on these data, it can be concluded that the system that has been developed has successfully met 8 aspects of testing using ISO 25010.